Manga Studio for dummies - Hills, Doug (--For dummies., 2008)
"Written by a working digital artist, Manga Studio For Dummies covers both Manga Studio Debut and EX versions. As an added bonus, it even gives you a peek into the world of manga and comics in general. With the help of Manga Studio For Dummies, you just might find yourself among the comic artists whose work populates the Web and gathers thousands of fans!"--Resource description page